2017
DOI: 10.1186/s12891-017-1742-7
|View full text |Cite
|
Sign up to set email alerts
|

Silver-coated modular Megaendoprostheses in salvage revision arthroplasty after periimplant infection with extensive bone loss – a pilot study of 34 patients

Abstract: BackgroundHip and knee replacements in patients with bone defects after infection correlates with high rates of reinfection. In this vulnerable patient population, the prevention of reinfection is to be considered superordinate to the functionality and defect bridging. The use of silver coating of aseptic implants as an infection prophylaxis is already proven; however, the significance of these coatings in septic reimplantation of large implants is still not sufficiently investigated.MethodsIn a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series. 4,5,20,22,23 The overall 12 % infection rate of the presented study is almost identical to the previously published series of mixed primary resections with revision arthroplasty where Glehr et al 27 reported an infection rate of 12.5 % among 32 patients who had been treated with MUTARS® silver-coated endoprostheses and Wafa et al 18 reported an overall postoperative infection rate of 11.8 % in the silver-coated group of 85 Agluna-Stanmore Implants. Likewise, Schmolders et al 4 had to perform revision operations due to infection in 10 % of their implanted silver-coated MUTARS® endoprostheses after a median follow-up of 24 months for primary or metastatic oncological patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series. 4,5,20,22,23 The overall 12 % infection rate of the presented study is almost identical to the previously published series of mixed primary resections with revision arthroplasty where Glehr et al 27 reported an infection rate of 12.5 % among 32 patients who had been treated with MUTARS® silver-coated endoprostheses and Wafa et al 18 reported an overall postoperative infection rate of 11.8 % in the silver-coated group of 85 Agluna-Stanmore Implants. Likewise, Schmolders et al 4 had to perform revision operations due to infection in 10 % of their implanted silver-coated MUTARS® endoprostheses after a median follow-up of 24 months for primary or metastatic oncological patients.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the results in revision arthroplasty patients are difficult to analyse within or between different centres due to different diagnostic methods of infection (e.g., sonication), perioperative antibiotic regiments, number of previous surgical procedures and pre-existing infections. All these limitations were also present in all other recent studies of this topic [1][2][3][4][5][6][19][20][21][22][23][24] where the infection-rate variability of silver-coated implants was larger between different patient populations (primary resection, metastases, revision, previous infection) and anatomical localizations than between different implant types (silver-coated vs. non-coated). 2 However, within each selected patient population and anatomical localization, silver-coated implants have consistently shown lower infection rates in comparison to other implants 18,[25][26] and our results corroborate these findings in the setting of an independent institution with longer follow-up from previous smaller patient series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent systematic review reported a tendency to a lower PJI rate with silver-coated hip megaprostheses primarily used in tumor indications [179]. These implants have also been used after PJI in patients with extensive bone loss [180]. However, the overall evidence in favor of using silver-coated implants is still insufficient [181].…”
Section: Anti-infective Implantmentioning
confidence: 99%
“…In a retrospective analysis of 34 patients, Zajonz et al [ 30 ] demonstrated that the rate of reinfection of modular mega-endoprostheses on hip and knee joints can be reduced by the use of silver-coated implants. Reinfection time can also be delayed by utilizing silver-coated implants.…”
Section: Infection Prevention and Osseointegration—bioactive Glassmentioning
confidence: 99%